Brand Equity dan Labelisasi Halal dalam Pengaruhnya Terhadap Minat Beli Produk Lifebuoy - Mega Rachma Kurniaputri (Jurnal Ilmiah Ekonomi Islam, 2020)
Brand equity is one of the most critical issue of marketing. It has four indicator such as brand awareness, brand loyalty, brand associations and perceived value which affect purchase intention. However in Indonesia, brand equity is not the only factors that affect customer intention to purchase. One of the most important factor is halal label because the majority of population is Muslim who wanted halal guarantee of the product before buying and consuming. Therefore, the purpose of this paper is to determine of how brand equity and halal label affect purchase intention of Lifebuoy products. The survey conducted on Muslim students of Universitas Pendidikan Indonesia which distributed online. By using multiple linear regression techniques to analyze the data, the result indicates that brand equity has positive significant effect to purchase intention. Meanwhile halal label has negative significant effect to purchase intention of Muslim student Universitas Pendidikan Indonesia.